2022
DOI: 10.3390/ph15060648
|View full text |Cite
|
Sign up to set email alerts
|

Novel Effects of Statins on Cancer via Autophagy

Abstract: Cancer is one of the main causes of death globally. Most of the molecular mechanisms underlying cancer are marked by complex aberrations that activate the critical cell-signaling pathways that play a pivotal role in cell metabolism, tumor development, cytoskeletal reorganization, and metastasis. The phosphatidylinositol 3-kinase/protein kinase-B/mammalian target of the rapamycin (PI3K/AKT/mTOR) pathway is one of the main signaling pathways involved in carcinogenesis and metastasis. Autophagy, a cellular pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 199 publications
0
9
0
Order By: Relevance
“…Autophagy is a biological process through which cells keeps balance in the homeostasis via the lysosomal degradation during cellular development and in the stress conditions [ 33 , 34 ]. It is generally considered a survival mechanism through which cells remove unwanted, misfolded, or aggregated proteins; damaged organelles; and intracellular pathogens [ 35 , 36 ], and autophagic cell death is considered a nonapoptotic cell death [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a biological process through which cells keeps balance in the homeostasis via the lysosomal degradation during cellular development and in the stress conditions [ 33 , 34 ]. It is generally considered a survival mechanism through which cells remove unwanted, misfolded, or aggregated proteins; damaged organelles; and intracellular pathogens [ 35 , 36 ], and autophagic cell death is considered a nonapoptotic cell death [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The induced activation of autophagy by statins might exert a significant and robust influence, diminishing their anti-cancer efficacy. This process is under the regulation of two signaling pathways: the mammalian target of rapamycin (mTOR) and AMPK [78].…”
Section: Basic Understanding Of the Molecular Mechanism Of The Anti-c...mentioning
confidence: 99%
“…Considering the dual role of autophagy in hepatocellular carcinoma (HCC), the importance of sustaining balanced autophagy activity within the PI3K/AKT/mTOR pathway to enable statins to stimulate autophagy in HCC. This action triggers an autophagic response mechanism due to the use of statins on the PI3K/AKT/mTOR signaling pathway [78].…”
Section: Basic Understanding Of the Molecular Mechanism Of The Anti-c...mentioning
confidence: 99%
“…The use of statins was associated with a slightly lower overall cancer incidence compared with nonusers and those who took other lipid-lowering medications [ 64 , 65 ]. In-vitro and in-vivo studies revealed that statins might be effective in cancer prevention and/or treatment via inhibiting tumor growth and inducing apoptosis [ 66 , 67 ]. Further, statins showed cytotoxic and antiproliferative effects against in several human cancer cell lines [ 66 , 68 , 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro and in-vivo studies revealed that statins might be effective in cancer prevention and/or treatment via inhibiting tumor growth and inducing apoptosis [ 66 , 67 ]. Further, statins showed cytotoxic and antiproliferative effects against in several human cancer cell lines [ 66 , 68 , 69 ]. Furthermore, statins treatment upregulated the expression of the proapoptotic proteins and downregulated the expression of antiapoptotic proteins in tumor cells [ 70 ].…”
Section: Introductionmentioning
confidence: 99%